(untitled) (European Journal of Education and Psychology, 2022)
Introduction Current status of research on social anxiety and relationship with psychoeducational variables: An international perspective Vicente E. Caballo and Isabel C. Salazar............................................................................3 Articles Do School-Based Accommodations Mitigate Anxiety-Related School Impairment for Socially Anxious Youth? Sophie R. Martel, Marissa M. Falcone, Rebecca G. Etkin, Carla E. Marin,Eli R. Lebowitz y Wendy K. Silverman...........................................................................7 Impact of School Transition Stressors on Hispanic Adolescents’ Symptoms of Social Anxiety and Depression: Repetitive Negative Thinking as a Potential Mediator Annette M. La Greca y Evan T. Burdette.........................................................................23 Social anxiety profiles and academic self-attributions in secondary school students. What are we really talking about? Theoretical, methodological, and statistical Dori J. A. Urbán, José M. García-Fernández, Aitana Fernández-Sogorb y Candido J. Ingles................................................................................43 Adolescents’ interpersonal cognition and self-appraisal of their own anxiety in an imagined anxiety-provoking classroom presentation scenario: Gender differences Klaus Ranta, Mauri Inkinen, Eero Laakkonen, Hanna-Riitta Ståhl, Niina Junttila y Päivi M. Niemi .......................................................................................572 Relationship between Social Anxiety Symptoms and Behavioral Impairment in Adolescents: The Moderating Role of Perfectionism and Learning Motivation Satoko Sasagawa y Cecilia A. Essau................................................................................79 The predictive ability of school refusal on high social anxiety in Chilean adolescents Mariola Giménez-Miralles, Nelly Lagos-San Martín y Carolina Gonzálvez.........................................................97 A qualitative study of social anxiety and impairment amid the COVID-19 pandemic for adolescents and young adults in Portugal and the US Samantha Coyle, PhD, Paula Vagos, PhD, Carrie Masia Warner, PhD, Joana Silva, PhD, Ana Xavier, PhD, Grace Martin, Jessica Wimmer,Avi Kalver, Britney Jeyanayagam, Helen-Maria Lekas, PhD, Ana Ganho-Ávila, Luiza Lima & Ana Santos Henrique .......................................................................................115